2013
DOI: 10.2528/pierc13042302
|View full text |Cite
|
Sign up to set email alerts
|

Novel Method to Detect and Recover the Keystrokes of Ps/2 Keyboard

Abstract: Computer keyboards are often used to transmit confidential data such as passwords. The sensitive information such as keystrokes could be recovered by using the electromagnetic (EM) waves from the electronic components of the keyboard. In this paper, we have investigated the information leakage on the ground line of the PS/2 serial cable due to crosstalk and radiative coupling. The coupling principles are analyzed firstly. And then, through the experiments we found that the signals of keystrokes could leak to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…A. Non-electromagnetic side-channels 1) Power line: Du et al [18], have demonstrated that it is possible to recover the keyboard data bus by studying its fingerprint on a power line. The measured consumption is a combination of keyboard consumption and consumption of other components.…”
Section: Analysis Of Non-electromagnetic Side-channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…A. Non-electromagnetic side-channels 1) Power line: Du et al [18], have demonstrated that it is possible to recover the keyboard data bus by studying its fingerprint on a power line. The measured consumption is a combination of keyboard consumption and consumption of other components.…”
Section: Analysis Of Non-electromagnetic Side-channelsmentioning
confidence: 99%
“…Since analysis is aimed at determining a link between power consumption and the data being processed, only dynamic power is relevant. As static power is mostly Side-channel emanation Power line (IV-A1) Keyboard [18] Internal Components [19] [20] Crypto system [21] constant, it is straightforward to use total power as a possible side-channel. SPA is based on the direct interpretation of power consumption measurements since each processor operation has a different trace.…”
Section: Analysis Of Non-electromagnetic Side-channelsmentioning
confidence: 99%
“…In 2009, Vuagnoux eventually obtained a significant result of 95% restoration at 20 meters by using the leaked EM waves from a PS/2 keyboard [51]. In the early 2010s, more advanced research on the radiated EM waves of keyboard keystrokes was actively conducted [10,52].…”
Section: Backgrounds 21 Research On Tempestmentioning
confidence: 99%
“…Wang and Yu analyzed a representative control circuit of keyboards by focusing on the PS/2 keyboard protocol in order to find the sensitive signals causing CE [11]. A recent study on CE of keyboard, which investigates the information leakage on the ground line of the PS/2 serial cable, is presented in 2013 [10]. It has been shown that the keystroke signals might leak to ground line network which then be recovered on the other power outlets sharing the same electric line.…”
Section: Types Of Compromising Emanationsmentioning
confidence: 99%
“…In the paper, van Eck reconstructed the Cathode Ray Tubes (CRT) screen content at a distance by using low-cost home built equipment. Furthermore, attacks to recover information from RS232 cable [6], Liquid Crystal Display (LCD) [7], laser printer [8], keyboard [9], [10], and [11] have been carried out.…”
Section: Introductionmentioning
confidence: 99%